Gattis celebrate 50th anniversary (Raton Range Raton, New Mexico, 1992)
Newspaper Article on the 50th Anniversary of Larry and Ann Gatti.
Master list item #: 70
File location is in the Raton File Cabinet
Keywords: Gatti, Larry; Gatti, Ann; Gatti, Mike; Gatti, Allen Larry; Gatti, UBerta; Gatti, Alene Elizabeth; Gatti, Sharon Ruth; Beck, Laresa Ann; Beck, Ginger Marie; Carson, Tom; Carson, Sharon Ruth; Gatti, Matthew Thomas; Gatti, Christopher Ryan; Gatti, Stanlee R; Holiday Classic Motel; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico